The archaeology of utopian and intentional communities - Kozakavich, Stacy C. (The American experience in archaeological perspective, 2017)
This volume describes and discusses historical archaeologists' contributions to our understanding of intentional communities throughout American history. Structured according to the scale of methodological focus - from settlement patterns and landscape, to the built environment, to artifact studies - the case studies presented in this volume will give readers a thorough introduction to archaeological research to date in this field